(untitled) (Zoo Botanica, 2025)
Temporal planting windows and plants spatial arrangements strongly modulates soybean development and productivity. A two-year field experiment was performed at the Ayub Agriculture Research Institute (AARI), Faisalabad, using soybean variety “AARI Soybean” under an RCBD spilt-plot design to examine the responses of two sowing date (15 July and 30 July) and three row spacing (30,45, and 50cm). The results showed that early sowing date (15th July) significantly improved plant height, number of pods per plant, seed per pod, 100-seed weight, and grain yield over late sowing, which expose plants to heat stress and reduced reproductive efficiency. Among row spacing, wider spacing (45-50 cm) consistently produced higher plant height, more pods per plant, better seed set, with a greater seed weight and superior grain yield due to improved light penetration reduced competition, and in hands canopy microclimate. The current study concluded that early sowing date with higher row spaces is the best option to get higher soybean yield. This research can enhance soybean adaptability under different climatic conditions.